2010
DOI: 10.1098/rstb.2009.0274
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of species: insights from the ecological genomics of lake whitefish

Abstract: In contrast to the large amount of ecological information supporting the role of natural selection as a main cause of population divergence and speciation, an understanding of the genomic basis underlying those processes is in its infancy. In this paper, we review the main findings of a long-term research programme that we have been conducting on the ecological genomics of sympatric forms of whitefish (Coregonus spp.) engaged in the process of speciation. We present this system as an example of how applying a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
317
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(335 citation statements)
references
References 110 publications
(175 reference statements)
15
317
0
Order By: Relevance
“…Other minor incompatibilities could still exist, which would account for the differential expression of genes observed in the healthy backcross fish versus parental types. Along this line, we previously observed that a least one locus associated with embryonic mortality is also linked to a regulation (expression Quantitative Trait Locus, eQTL) hotspot and may harbor a major regulatory gene with strong pleiotropic effect on the expression of numerous genes (Bernatchez et al, 2010), thus representing a possible mechanism explaining the genome-wide disruption of regulation in hybrids.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Other minor incompatibilities could still exist, which would account for the differential expression of genes observed in the healthy backcross fish versus parental types. Along this line, we previously observed that a least one locus associated with embryonic mortality is also linked to a regulation (expression Quantitative Trait Locus, eQTL) hotspot and may harbor a major regulatory gene with strong pleiotropic effect on the expression of numerous genes (Bernatchez et al, 2010), thus representing a possible mechanism explaining the genome-wide disruption of regulation in hybrids.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, early in ontogeny, normal and dwarf fish are phenotypically and ecologically indistinguishable (Chouinard and Bernatchez, 1998;Bernatchez, 2004). At the same time, hybrid whitefish experience striking fitness consequences of genomic incompatibilities and ongoing reproductive isolation (increased mortality, disruption of hatching time and reduced sperm performance, Rogers and Bernatchez, 2006;Whiteley et al, 2009;Bernatchez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These false positives lead us to conclude incorrectly about the genetic bases of the populations or phenotypes being studied. This is a central argument for leveraging the framework of parallel evolution (Bernatchez et al, 2010;Elmer & Meyer, 2011). Replicate Hydrobiologia (2016) 783:191-208 203 phenotypes in the parallel evolution framework are so called 'natural evolutionary experiments' (Doughty, 1996) used in comparative approaches as a way to tackle the challenges of evolutionary time scales and environmental stochasticity.…”
Section: Ecological Genomics For Predictionsmentioning
confidence: 99%
“…These morphotypes differ in a range of ecologically relevant traits such as body size, head shape, parasite load immunogenetics, growth rate, spawning timing and/or behaviour, and lipid content of the muscle (Skúlason et al 1996;Jonsson & Jonsson, 2001;Adams & Huntingford, 2004;Goetz et al, 2010Goetz et al, , 2014Gudbrandsson et al, 2015). Many of these traits are in fact archetypal of intralacustrine differentiation in other freshwater fishes, with similar components found from stickleback fishes (Schluter, 1993;Willacker et al, 2010) and coregonids [lake (Bernatchez et al, 2010) or European whitefish (Østbye et al, 2006)] in the northern hemisphere, to cichlid fishes in the Neotropics (Elmer et al, 2014) and Africa (Hulsey et al, 2013). However, among the northern fishes, charr are the species in which multiple sympatric morphs are found most abundantly (Klemetsen, 2010).…”
Section: Introgressionmentioning
confidence: 99%